Pathogenic variants in the COCH gene that lead to hearing loss and vestibular deficit: Update on DFNA9 and introducing DFNB110 - Van Rompaey, Vincent; Gommeren, Hanne; Bosmans, Joyce; Verdoodt, Dorien; Janssens de Varebeke, Sebastien; Vrieze, Erik de; Pennings, Ronald; van de Berg, Raymond; Lammers, Marc; Vanderveken, Olivier M.; Fransen, Erik; Van Camp, Guy; et al. (B-ENT)
DeaFNess Autosomal Dominant 9 is an autosomal dominant hereditary non-syndromic form of progressive sensorineural hearing loss often associated with vestibular dysfunction. It is caused by over 30 heterozygous pathogenic variants in the COCH gene, which encodes cochlin. The DeaFNess Autosomal Dominant 9 p.Pro51Ser variant is the most prevalent cause of adult-onset hereditary hearing loss in Belgium and leads to severe-to-profound sensorineural hearing loss and bilateral vestibulopathy. The recent discovery of homozygous pathogenic variants in the COCH gene-leading to loss-of-function of cochlin-has resulted in the designation of a new autosomal recessive disorder called DFNB110. Cochlear implantation should be considered as soon as patients no longer benefit from a hearing aid because all carriers show a natural evolution toward deafness, a condition that is associated with a higher risk of accelerated cognitive impairment. Moreover, cochlear implantation candidates fulfilling the most recent reimbursement criteria in Belgium have better speech understanding after cochlear implantation when compared to the previous reimbursement criteria. Vibrotactile feedback of the gravity vector-provided by a balance belt-can significantly improve balance and mobility for the bilateral vestibulopathy symptoms. A vestibulocochlear implant is a modified research cochlear implantation thatnext to capturing hearing-is also able to capture motion. The dominant inheritance pattern and non-haploinsufficiency disease mechanism of DeaFNess Autosomal Dominant 9 indicate that suppressing translation of mutant COCH transcripts has high therapeutic potential, which might even prevent hearing impairment. This review will highlight recent insights and future perspectives related to DeaFNess Autosomal Dominant 9 and DFNB110.